Implementation Of The Utmanian Turkish Method In Improving The Quality Of Memorializing The Qur'an - Fatih Hanabila Aliya; Masrur Anhar; Marhamah Marhamah (LPPM Universitas PGRI Sumatera Barat, 2024)
As time goes by, the world has experienced many changes. One thing that is very striking is seen in the field of technology. But not in the knowledge of Al-Qur’an. Because it has its own special feature which is that it is eternal until the Day of Judgment. It is different from other worldly sciences because it must follow developments with the times. One way to keep Al-Qur’an is to memorize it. And to memorize the Al-Qur'an, a method is needed to achieve the goal of quality memorization or what is called mutqin. This qualitative research uses primary data obtained through documentation, observation and interview methods, and the analysis uses qualitative descriptive methods. The results of the research show that the application of the Turki Utsmani Method has improved the quality of students' memorization of the Al-Qur'an at the Tahfidz Al Ishlah Islamic Boarding School, Jakarta. The Turki Utsmani method has proven effective in selecting students to become prayer leaders, because they have good memorization qualities and have been proven to become prayer leaders. The memorization system makes the last page of each juz the beginning, making memorization stronger.